Carbapenemase-producing Enterobacteriaceae digestive carriage at hospital readmission and the role of antibiotic exposure. Issue 1 (May 2019) - Evain, S.; Bourigault, C.; Juvin, M.-E.; Corvec, S.; Lepelletier, D.
Summary: Background: Colonization by carbapenemase-producing Enterobacteriaceae (CPE) may persist for several months after hospital discharge, especially in patients with altered microbiota. Aim: To identify how many previously OXA-48 CPE-positive patients identified during an outbreak period were readmitted; to evaluate their CPE-positive or -negative digestive tract colonization at hospital readmission and during readmission stay; and to assess the role of antibiotic exposure on their CPE colonization status during readmission. Methods: All CPE cohort patients from June 2013 to May 2016 ( N  = 189) were registered in a survey database and were systematically identified at readmission by a daily informatics and alert program using specific hospital population number. Each cohort patient was systematically screened for CPE colonization on the day of readmission and then weekly if the length of stay was more than six days. Findings: In all, 114 (60.3%) patients previously CPE-colonized were readmitted to our hospital. Excluding the 12 patients who were not screened because their period of readmission was <24 h, 88 patients were negative (86.3%) and 14 were positive (13.7%) for CPE colonization at first hospital readmission. The 14 CPE-positive patients did not change their infectious status and remained CPE-positive during the study period. Of the 88 negative patients, 65 remained negative during the study period, and 23 subsequently became CPE-positive after the negative readmission screening. CPE-positive colonization was significantly associated with antibiotic exposure during readmission periods ( P < 0.001). Conclusion: Negative screens at hospital readmission did not necessarily predict resolution of CPE carriage. Antibiotic exposure appears to influence the risk of remaining CPE positive.